A Hinge in Eurasia: Regional infrastructure and geopolitical changes. - Labardini, Rodrigo (SÉCULO XXI: Revista de Relações Internacionais - ESPM, 2024)
ABSTRACT While Asia and Europe lie in the same landmass, they have always been considered two separate and distinct continents. The land route between East (China) and West (Europe) must traverse the Caspian Sea or its northern (Russia) or southern (Iran) shores —with heightened attention due to international sanctions and the Russian invasiton of Ukraine. While geography dominates one’s environment, it is one’s will which molds destiny. Geography without infrastructute is a dot on a map. A door lies between East and West: the Caspian Sea, with the Caucasus as its hinge, and infrastructure as its lubricant.